2019
DOI: 10.1111/apt.15297
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review with meta‐analysis: efficacy and safety of oral Janus kinase inhibitors for inflammatory bowel disease

Abstract: Background: Janus kinase (JAK) inhibitors represent a novel therapeutic class for treatment of inflammatory bowel disease. Aims:To determine the efficacy and safety of JAK inhibitors compared to placebo for the treatment of Crohn's disease (CD) and ulcerative colitis (UC). Methods:PubMed, Embase and CENTRAL were systematically searched to November 1, 2018. Randomised placebo-controlled trials (RCTs) of JAK inhibitors in adult patients with CD or UC were eligible. Open-label extension studies without a placebo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 57 publications
2
51
0
1
Order By: Relevance
“…The rate of infections was comparable with vedolizumab (IBD: 38 per 100 patient years) and ustekinumab (CD: 36 per 100 patient years) . However, the limited follow‐up period could have biased these results as JAK inhibitors are associated with an increased risk of infections when compared with placebo (RR 1.40 [95% CI 1.18‐1.67], P < 0.0001) …”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The rate of infections was comparable with vedolizumab (IBD: 38 per 100 patient years) and ustekinumab (CD: 36 per 100 patient years) . However, the limited follow‐up period could have biased these results as JAK inhibitors are associated with an increased risk of infections when compared with placebo (RR 1.40 [95% CI 1.18‐1.67], P < 0.0001) …”
Section: Discussionmentioning
confidence: 91%
“…A recent review of clinical trials showed a comparable safety profile of tofacitinib when compared with vedolizumab and anti‐TNF with the exception of herpes zoster infections/reactivations . Another systematic review of clinical trials showed no increased risk of adverse events when JAK inhibitors were compared with placebo . However, in these reviews, not the number of adverse events but the number of patients with adverse events was compared.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, histologic improvement or remission were more frequent in upadacitinib-treated patients compared to placebo. 64,65 Filgotinib, a selective JAK1 inhibitor, is under investigation in a phase 2b/3 in patients with moderate-to-severe UC (NCT02914522). Currently, several other selective JAK1 inhibitors, such as SHR0302 and itacitinib (NCT03675477; NCT03627052), TYK2 inhibitor, such as BMS-986165 (NCT03934216) or gut-selective pan-JAK inhibitors such as TD-1473 (NCT03635112) are under investigation, and many others are being developed by the industries.…”
Section: Other Jak Inhibitors In Ulcerative Colitismentioning
confidence: 99%
“…61 Excluding peficitinib, no complete publications of clinical data are currently available for the other compounds. 64…”
Section: Other Jak Inhibitors In Ulcerative Colitismentioning
confidence: 99%
“…We were interested to read the study by Ma et al 1 reporting that a janus kinase (JAK) inhibitor was effective induction therapy for a refractory population of adults with ulcerative colitis (UC) and Crohn's disease (CD). 2,3 Despite an increased risk of infection, with particular concern over herpes zoster, JAK inhibition was not associated with an increased risk of adverse events (AEs).…”
Section: Editorsmentioning
confidence: 99%